Probing attack of share‐serial threshold implementation of advanced encryption standard. Issue 9 (1st May 2019) - Sugawara, T.; Li, Y.; Sakiyama, K.
Abstract : The authors present the first security evaluation of the side‐channel attack countermeasure called the share‐serial threshold implementation proposed by Wegener and Moradi. In the share‐serial threshold implementation, all the component functions are processed using a unified circuit thereby reducing total circuit area. They show that the share‐serial threshold implementation is vulnerable to probing attack using a single probe. In the proposed attack, an attacker places a single probe on a wire in the unified circuit and read the target wire over multiple cycles. The attacker can recover unshared 1‐bit intermediate value by combining the measured data. The attack highlights an interesting difference between side‐channel analysis and probing attack. The authors also evaluate the number of cipher calls to attack the block cipher advanced encryption standard (AES).